Effect of X-ray treatments on Salmonella enterica and spoilage bacteria on skin-on chicken breast fillets and shell eggs. (November 2015) - Mahmoud, Barakat S.M.; Chang, Sam; Wu, Yuwei; Nannapaneni, Ramakrishna; Sharma, Chander Shekhar; Coker, Randy
Abstract: The objectives of this study were to determine the efficacy of X-ray irradiation on the inactivation of a 3-strain mixture of Salmonella enterica (S. Enteritidis E190-88, S. Typhimurium ATCC 14028, and S. Montevideo ATCC 8387) using an RS 2400 X-ray system on chicken breast fillets and shell eggs and to evaluate the effect of X-ray treatments on the shelf life of chicken breast fillets and shell eggs during 20 day storage at 5 °C (chicken breast fillets (25 g) or whole shell egg samples were treated with the 0.1 and 2.0 and 0.1 and 1.0 kGy, for chicken and shell eggs, respectively, and stored at 5 °C for 20 days. Samples were examined for psychrotrophs and mesophiles counts at 0, 5, 10, 15, and 20 days). In this study, the skin on chicken breast fillets (25 g) or whole shell egg (50 g) samples were inoculated by immersing in 0.1% peptone water that contained 10 8−9  CFU ml −1 of a 3-strain mixture of S. enterica for 1 min in a biosafety cabinet. The samples were then air dried at 22 °C for 30 min (to allow bacterial attachment) in the biosafety cabinet prior to X-ray treatments (0.0, 0.1, 0.5, 1.0, and 2.0 kGy). The surviving Salmonella populations on the chicken breast fillets and the shell egg samples were evaluated using a nonselective medium (tryptic soy agar) for 6 h with xylose lysine desoxycholate (XLD) (Difco, Becton Dickinson) selective medium overlay. The plates were then incubated for an additional 18 h at 37 °C. The colonies were counted and the results were expressed as log CFU/g or egg. The results indicated that the 0.5 kGy X-ray treatment significantly reduced the Salmonella population by 1.9 and 3.0 log reduction on chicken breast meat and shell egg samples, respectively, with greater than a 6 log CFU reduction being achieved with 2.0 and 1.0 kGy X-ray for chicken and shell eggs, respectively. Furthermore, treatment with X-ray significantly reduced the initial inherent microbiota on chicken breast fillets and shell eggs and inherent levels were significantly (p < 0.05) lower than the control sample throughout the shelf-life storage at 5 °C for 20 days. These results indicated that X-ray is a promising antimicrobial technology for the poultry and egg industries. Highlights: 0.5 kGy X-ray reduced the Salmonella population by 1.9 log on chicken breast. 0.5 kGy X-ray reduced the Salmonella population by 3.0 log on shell egg. 1.0 kGy X-ray reduced the Salmonella population by > 6 log on shell egg. 2.0 kGy X-ray reduced the Salmonella population by > 6 log on chicken breast. 1.0–2.0 kGy X-ray kept inherent microbiota at low level for 20 days at 5 °C.